2009
DOI: 10.1007/s12035-008-8049-5
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the Hippocampal Mossy Fiber Synapse for the Treatment of Psychiatric Disorders

Abstract: It is widely known that new neurons are continuously generated in the dentate gyrus of the hippocampus in the adult mammalian brain. This neurogenesis has been implicated in depression and antidepressant treatments. Recent evidence also suggests that the dentate gyrus is involved in the neuropathology and pathophysiology of schizophrenia and other related psychiatric disorders. Especially, abnormal neuronal development in the dentate gyrus may be a plausible risk factor for the diseases. The synapse made by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
53
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 63 publications
(55 citation statements)
references
References 194 publications
2
53
0
Order By: Relevance
“…The prominent synaptic facilitation plays a critical role in regulation of the CA3 neuronal activity and plasticity by MF (9,10). The dematuration affected both of these important physiological properties of mature GCs, thereby potentially impeding proper functioning of the adult hippocampus (43). Similar changes in GC functions and/or in the state of GC maturation have been demonstrated in mice disrupted for the gene encoding alpha-CaMKII (27), brain-derived neurotrophic factor (44), or the glutamate receptor subunit GluK2/GluR6 (10,45).…”
Section: Discussionmentioning
confidence: 99%
“…The prominent synaptic facilitation plays a critical role in regulation of the CA3 neuronal activity and plasticity by MF (9,10). The dematuration affected both of these important physiological properties of mature GCs, thereby potentially impeding proper functioning of the adult hippocampus (43). Similar changes in GC functions and/or in the state of GC maturation have been demonstrated in mice disrupted for the gene encoding alpha-CaMKII (27), brain-derived neurotrophic factor (44), or the glutamate receptor subunit GluK2/GluR6 (10,45).…”
Section: Discussionmentioning
confidence: 99%
“…Given that the DG is the site of highest DISC1 expression in the adult brain (11) and has been implicated in SCHZ pathophysiology (12,35), we examined the development, maturation, and excitability of dentate GCs as well as synaptic transmission and plasticity in the MF/CA3 circuit. We elucidated the impact of the pathogenic DISC1 mutation by applying an array of morphological, neurophysiological, biochemical, and cellular assays to an etiologically valid mouse model of this mutation.…”
Section: Discussionmentioning
confidence: 99%
“…Although the pattern of MF lamination has not been explicitly probed in patients with SCHZ, one study has reported lower numerical density of MFTs in CA3 (44), and another study showed lighter overall staining with an MF specific marker (45) consistent with changes occurring in this pathway. More broadly, neuropathological studies have found a number of variable and modest disturbances in the overall DG-CA3 region, including reduced dendritic arborization (13,14), implicating this region in SCHZ pathogenesis (12,35).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stress, which is generally thought to precipitate psychiatric disorders including depression, changes the structure and functions of the mossy fiber synapse (Chen et al, 2010;Kobayashi, 2010;Magariños et al, 1997). These lines of evidence suggest that the mossy fiber synapse could be an important target for SSRIs and other antidepressant drugs (Kobayashi, 2009(Kobayashi, , 2010.…”
Section: Introductionmentioning
confidence: 99%